Pengembangan Panduan Praktikum Perkerasan Jalan Raya Campuran Asphalt Concrete-Wearing Course (AC-WC) Menggunakan Kapur Padam sebagai Bahan Tambah Filler - Rifanli Labaso; Fadly Achmad; Frice L. Desei (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Asphalt Concrete – Wearing Course (AC-WC) mixtures are widely used as surface layers due to their water resistance and high durability. This study aims to analyze the effect of adding hydrated lime as a filler on the Marshall properties of AC-WC mixtures. The hydrated lime was added in variations of 1.0%, 1.5%, 2.0%, 2.5%, and 3.0%. Additionally, this research produced a practical module for road pavement construction based on filler variations. The research method involved laboratory testing using the Marshall Test to determine the mixture characteristics. Materials used included coarse aggregate, fine aggregate, and asphalt from PT Petra Anugerah Sejahtera Pulubala, and hydrated lime from Tenilo Subdistrict, Hulonthalangi District. Testing was conducted at the Civil Engineering Laboratory of Universitas Negeri Gorontalo. Results showed that the mixture without hydrated lime had a density of 2.6 gr/cc, VIM of 3.88%, VMA of 15.99%, VFB of 75.74%, stability of 2305.04 kg, flow of 3.47 mm, and MQ of 678.78 kg/mm. The addition of hydrated lime increased density, VFB, Marshall stability, and MQ, while decreasing VIM, VMA, and flow. The mixture with 1.5% hydrated lime content produced the most optimal results, with stability reaching 2617.20 kg and MQ of 792.18 kg/mm. In conclusion, hydrated lime is effective as an alternative filler to improve the performance of AC-WC mixtures and support the utilization of local resources. The developed practical module can also assist in conducting field tests on AC-WC mixtures.